Enhancing mean estimators in median ranked set sampling with dual auxiliary information - Randa Alharbi; Manahil SidAhmed Mustafa; Aned Al Mutairi; Mohamed Hussein; M. Yusuf; Assem Elshenawy; Said G. Nassr (Heliyon, 2023)
When measuring the research variable is complicated, expensive, or problematic, median ranked set sampling (MRSS) is often utilized since it is straightforward to rank the components using a low-cost sorting criterion. Using this sampling scheme, many authors considered the problem of population mean estimation with a single auxiliary variable in order to obtain more precised estimators than the traditional ratio type regression estimators. In this article, we extend their ideas based on regression approach using two auxiliary variables and introduce a new regression-type estimator along with its theoretical expression of minimum mean square error (MSE). The suggested estimator's applicability is demonstrated using both simulated and real-world data sets.